Produksi kompos bokashi PPUPIK sebagai unit profit UNM - Adnan Adnan; Nani Kurnia; Hamka L; Sitti Saenab; Ahmad Jihadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Bokashi compost production is carried out at the Biology Experimental Farm Laboratory as part of the Campus Intellectual Product Development Program (PPUPIK) which is one of the community service programs (PKM) of the Ministry of Research and High Education (Kemenristekdikti). This is motivated by problems encountered: (1) There is still a lack of good quality compost on the market, (2) Makassar has many horticultural and ornamental plant tips so that the demand for compost is also high, (3) compost production sites in Makassar is relatively small so that most compost in the market is obtained from other regions, thus increasing transportation costs and ultimately the price is more expensive. The method used is apprenticeship practical work, demonstrations, Forum Group discussions (FGD), and consultation. The results achieved are (1) apprentices have knowledge of compost, planting media and nutrition for good plant growth and development, (2) Apprentices have the skills to make Bokashi compost, (3) Apprentices have good production and marketing management skills good, (4) Producing bokashi compost that has good quality and adequate quantity.